Influence of simulated ocean warming on food consumption rates in the sea urchin species Arbacia lixula - Lenz, Mark; Roma, Joana; Schertenleib, Katrin; Ramalhosa, Patricio; Gestoso, Ignacio; Canning-Clode, Joao (PANGAEA, 2021)
This experimental study investigated the effects of ocean warming on food consumption rates in the sea urchins Arbacia lixula from Madeira Island to assess how the feeding pressure they exert may change under warmer ocean conditions. Additionally, in A. lixula, the relationship between temperature and the gonad index was examined to estimate potential future reproductive output. Over the course of25 days, 180 individuals of each species were exposed to temperatures between 22 °C and 31 °C in the laboratory. After 20 days, consumption rates were assessed in 48-h feeding trials. Gonad indices of A. lixula were determined on the last day of the experiment. Data contain information about place and time of the animal collection as well as laboratory experiment and information about temperature regimes, food consumption rates of Arbacia and information about gonad indices and the sex of the animals.
Keywords: Arbacia lixula; gonad index; invertebrate macro-grazer; Madeira; ocean warming; sea urchins